PEPDROID: Development of a Generic DREIDING‐Based Force Field for the Assessment of Peptoid Secondary Structures. Issue 12 (20th September 2018) - Hoyas, Sébastien; Lemaur, Vincent; Duez, Quentin; Saintmont, Fabrice; Halin, Emilie; De Winter, Julien; Gerbaux, Pascal; Cornil, Jérôme
Abstract: α‐Peptoids are peptido‐mimetic foldamers based on poly‐ N ‐substituted glycines that currently receive a growing interest due to their larger structural diversity, easier synthetic pathways, and larger thermal stability compared to peptides. An appropriate side chain appended to the nitrogen atoms is often crucial to constrain the peptoids into well‐defined and active rigid structures for applications. To shed light on the secondary structure of peptoids, accurate methods for structural characterization are mandatory and typically involve the association of circular dichroism and nuclear magnetic resonance spectroscopies. Molecular simulations can also prove highly complementary to rationalize the relationship between their primary and secondary structures, although much less studies have been reported to date compared to the knowledge accumulated on peptides. To this end, the PEPDROID force field has been developed based on the DREIDING force field, by incorporating a new set of parameters relative to (α and β) peptoids bearing different side chains. The ability of PEPDROID to assess the secondary structure of peptoids by generating Ramachandran‐like plots matching those previously obtained at a quantum‐chemical level for model systems has been demonstrated. For further sake of validation, it is demonstrated that PEPDROID can reproduce the experimental structures of either α‐ or β‐ peptoids . Abstract : Peptoids are peptide regioisomers constituting an emerging class of foldamers. Compared to peptides, the ability of peptoids to fold into well‐defined secondary structures is still poorly understood. Here, a new set of parameters proper to peptoids are introduced into the Dreiding force field to produce the PEPDROID force field, designed to get insight into their structural properties.